Biochar’s stability and effect on the content, composition and turnover of soil organic carbon - Han, Lanfang; Sun, Ke; Yang, Yan; Xia, Xinghui; Li, Fangbai; Yang, Zhifeng; Xing, Baoshan (Geoderma, 2020)
[Display omitted] •Stability of biochar was related with both biochar and soil properties.•Positive priming effect was common for manure biochar and sandy soil.•Manure-based and low temperature biochar more intensely promoted soil aggregation.•Influential mechanisms of biochar on HS amount and composition were proposed. Extensive application of biochar to soil exerts a profound effect on organic carbon (OC) in soils. However, the impact of biochar on the content and composition of OC has not been comprehensively summarized. This review provided a detailed examination on the stability of biochar and its effect on the amount, composition and turnover of soil OC, with key limitations and issues recognized. The direct input of labile and stable OC of biochar to soil OC pool, and indirect effects of biochar on soil OC by affecting soil physicochemical and biological properties were discussed. Both low stability of biochar and biochar-induced strong positive priming effect on OC mineralization were commonly observed in sandy soil added with biochar produced from manure at low temperature. The stable OC of biochar was composed of both aromatic OC and the OC fractions stabilized by soil minerals. Biochar mainly increased the formation of macro-aggregates, and this promotion was more intense for clayey soil added with manure-based low temperature-biochar. Additionally, potential influential mechanisms were proposed to explain the effect of biochar addition on amount and composition of humic substances in soils. This review will shed lights on the effect of biochar application on the amount, composition and turnover of native soil OC, and improve the understanding of the ecological effect of biochar on the soil functions.